Hematopoietic growth factors in oncology - Lyman, Gary H. (Gary Herbert) 1946-.; Dale, David C.; SpringerLink (Online service). (New York Springer, 2011)
No area of cancer supportive care better illustrates the advances in our understanding of cellular and molecular biology, genetic engineering and the development of more effective yet often more toxic cancer treatments than that of hematopoietic growth factors. Myelosuppressive agents, with their potential hematopoietic toxicities, remain the mainstay of systemic treatment for both metastatic and early stage cancer. Hematopoietic Growth Factors in Oncology reviews and integrates the major advances in our understanding of the underlying molecular biology and pharmacology of these agents along with the results of well designed and executed randomized controlled trials of the erythroid stimulating agents, the myeloid growth factors and the new thrombopoietic agents, each addressing a major threat associated with bone marrow suppression accompanying cancer treatment. "Hematopoietic growth factors have revolutionized the treatment of patients with a spectrum of cancers and benign bone marrow disorders. This text addresses the mechanism of action and clinical impact of these cytokines. Leading investigators in the field provide and update of current state of knowledge and future challenges." ? Steven T. Rosen, M.D. Series Editor.
pt. 1. Background : biology, physiology, and pharmacology -- pt. 2. The colony-stimulating factors -- pt. 3. The erythroid-stimulating agents -- pt. 4. The thrombopoietic agents -- pt. 5. Special considerations.
Electronic reproduction.
Keywords: Hematopoietic growth factors -- Therapeutic use; Cancer -- Chemotherapy; Electronic books